(3eHdZ GdfXQ hfJjLI GdacQs - (3GdcGXej, GdORahdj, CSO Gddg Hf ESeGYjd, J (B1220(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdQLGd bhGejf Ydi GdfSGA(B...(3gPG jG ENhGfj eHdZ GdfXQ hfJjLI GdacQ(B...(3hGdeSCdI gj Cfg EPG CbQ GdRhL HWdGb RhLJg GdeYjfI(B...(3adG QjH aj Cfg jbHd HGdfSHI Edjg hgd jbHd HGdfSHI EdjgG(B...s
(3BNQgG (B:s
(3hcGf Mce GdeQCI aj GdEQK Mce cd eWdbI KHJ WdGbgG HGdHjfI(B...s
(3JHUQI GdeDda (B:s
(3CQN dhaGJg aj GdPQjYI HSfI (B1237(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf(B:(3L(B1(3U(B203s
(3GdPQjYI(B:(3L(B19(3,U(B38(3,Qbe(B292s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis